EXCAVATION OF A SINGLE KURGAN UCHKENT IV - Gadziev, Murtazali Serazutdinovic; Malasev, Vladimir Ur'evic; Sajpudinov, Murad Sahbanovic; Abdulaev, Abdula Magomedovic; Abiev, Askerhan Kamalovic; Budajciev, Arsen Lahmanovic; Sausev, Kydyrali Bajramgazyevic (History, Archeology and Ethnography of the Caucasus, 2023)
In 2019, a joint archaeological expedition of the Scientific and Production Center for Tourism and Local Lore, the Institute of History, Archeology and Ethnography of the Dagestan Federal Research Center of the Russian Academy of Sciences and the Institute of Archeology of the Russian Academy of Sciences conducted rescue excavations of the single kurgan Uchkent IV, located in the reconstruction zone of the Grozny-Baku oil pipeline in the Kumtorkala district of the Republic of Dagestan. An outer stone crescent-shaped pavement, a stone sketch around and above burial 1 surrounded by a cromlech, and two burials in stone tombs (burials 1 and 2) were identified under the mound embankment. The funeral rite and the burial equipment preserved after the robbery allow us to attribute the main burial 1 and the time of the construction of the kurgan to the Middle Bronze Age. Intake burial 2 also refers to the Middle Bronze Age, but the almost complete absence of burial equipment does not allow to clarify its chronology. Kurgan Uchkent IV has close parallels with the Taular-gol kurgans in Caspian Dagestan, with which it is possible to form one chronological and cultural group associated with the Sulak (Prisulak) culture.The revealed details of the kurgan architecture and funeral rite, expressed in a combination of solar (cromlech) and lunar pavements around the central burial in a tomb surrounded by a dense stone coating that imitated a round embankment, are of particular interest. The oldest similar, stone and earthen, pavements in the Caucasus date back to the Eneolithic, they are found in the burial mounds of the Maykop cultural and historical community of the Early Bronze Age, as well as in the barrows of the Middle Bronze Age. It can be assumed that solar-lunar constructions are due to religious ideas about life and death, reflecting some cosmogonic binary representations of the carriers of this sometimes occurring ritual (archaic myths about the Sun and the Moon).
Keywords: Dagestan; kurgan; Middle Bronze Age; funeral rite; stone embankment; cromlech; lunar pavement